Using Attentional Control Theory to account for anxiety-related errors on musical performance tasks - Ruggiero, Matthew (Curtin University, 2012)
This research evaluated the effects of anxiety and distraction on attentional control during musical performances. Performers with moderate to high trait anxiety demonstrated reduced attentional control when exposed to distraction. This created impairments in the shifting function that favoured the musical pieces over a secondary task. These findings provide preliminary support for an Attentional Control Theory account of anxiety-related performance outcomes for musical tasks.